Alanine and glutathione targeting of dopamine- or ibuprofen-coupled polypeptide nanocarriers increases both crossing and protective effects on a blood–brain barrier model - Mária Mészáros; Thi Ha My Phan; Judit P. Vigh; Gergő Porkoláb; Anna Kocsis; Anikó Szecskó; Emese K. Páli; Nárcisz M. Cser; Tamás F. Polgár; Gábor Kecskeméti; Fruzsina R. Walter; Jens C. Schwamborn; et al. (Fluids and Barriers of the CNS)
Abstract Background Targeting the blood–brain barrier (BBB) is a key step for effective brain delivery of nanocarriers. We have previously discovered that combinations of BBB nutrient transporter ligands alanine and glutathione (A-GSH), increase the permeability of vesicular and polypeptide nanocarriers containing model cargo across the BBB. Our aim was to investigate dopamine- and ibuprofen-coupled 3-armed poly(l-glutamic acid) nanocarriers targeted by A-GSH for transfer across a novel human co-culture model with induced BBB properties. In addition, the protective effect of ibuprofen containing nanoparticles on cytokine-induced barrier damage was also measured. Method Drug-coupled nanocarriers were synthetized and characterized by dynamic light scattering and transmission electron microscopy. Cellular effects, uptake, and permeability of the nanoparticles were investigated on a human stem cell-based co-culture BBB model with improved barrier properties induced by a small molecular cocktail. The model was characterized by immunocytochemistry and permeability for marker molecules. Nanocarrier uptake in human brain endothelial cells and midbrain organoids was quantified by spectrofluorometry and visualized by confocal microscopy. The mechanisms of cellular uptake were explored by addition of free targeting ligands, endocytic and metabolic inhibitors, co-localization of nanocarriers with intracellular organs, and surface charge modification of cells. The protective effect of ibuprofen-coupled nanocarriers was investigated against cytokine-induced barrier damage by impedance and permeability measurements. Results Targeted nanoformulations of both drugs showed elevated cellular uptake in a time-dependent, active manner via endocytic mechanisms. Addition of free ligands inhibited the cellular internalization of targeted nanocarriers suggesting the crucial role of ligands in the uptake process. A higher permeability across the BBB model was measured for targeted nanocarriers. After crossing the BBB, targeted dopamine nanocarriers subsequently entered midbrain-like organoids derived from healthy and Parkinson’s disease patient-specific stem cells. The ibuprofen-coupled targeted nanocarriers showed protective effects against cytokine-induced barrier damage. Conclusion BBB-targeted polypeptide nanoparticles coupled to therapeutic molecules were effectively taken up by brain organoids or showing a BBB protective effect indicating potential applications in nervous system pathologies. Graphical Abstract